2008
DOI: 10.1002/hed.20758
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor satellite distance with prognosis and contralateral neck recurrence of tongue squamous cell carcinoma

Abstract: TSD is associated with local recurrence, contralateral neck metastasis, and the overall survival of patients with tongue cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…However, this concept has recently been challenged by several studies in which pathologically document that adequate margins cannot necessarily guarantee tumor cells are removed completely [62][63][64][65][66] and patients with clear margins do not always have good clinical outcomes, as local recurrence rates with clear margins in tongue cancer ranged from 4% to 18% [56,58,62]. As a result, there is not a single definition for an adequate resection margin.…”
Section: Surgical Margin Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this concept has recently been challenged by several studies in which pathologically document that adequate margins cannot necessarily guarantee tumor cells are removed completely [62][63][64][65][66] and patients with clear margins do not always have good clinical outcomes, as local recurrence rates with clear margins in tongue cancer ranged from 4% to 18% [56,58,62]. As a result, there is not a single definition for an adequate resection margin.…”
Section: Surgical Margin Statusmentioning
confidence: 99%
“…Therefore, tumors may leave distant tumor satellites beyond the surgical scope and lead to consequently local recurrence, cervical nodes metastasis, and poor outcomes when surgical margins are considered clear intraoperatively. Yang et al [64] reported that tumor satellites occurred in 92% of tumors and were significantly associated with betel nut exposure. Patients with TSD more or less than 0.5 mm had statistical significance for prognosis while patients with TSD >0.5 mm had a higher incidence of local recurrence, shorter intervals to neck recurrence, and a higher propensity to contralateral or bilateral cervical nodal metastasis.…”
Section: Tumor Satellites and Tumor Satellite Distancementioning
confidence: 99%
“…The histological features of OSCC may differ widely from area to area within the same tumour due to tumour heterogeneity and is subject to inter‐ and intraobserver disagreement 14 . There is general agreement that the most useful prognostic information can be deduced from the invasive front of the tumour, where the deepest and presumably most aggressive cells reside 5,8,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Regardless of advances in treatment modalities, the early detection of cancer still remains a challenge [1]. Carcinogenesis is a multistep and multifocal process involving clonal expansion and spreading of transformed cells [2][6]. Clinically, the number of patients having precancerous lesions is far more than those with malignant tumors.…”
Section: Introductionmentioning
confidence: 99%